Plain promise [large type] - Wiseman, Beth, 1962- (Wiseman, Beth, 1962- Daughters of the promise novel, 2009)
Sadie Fisher wonders if she'll ever find true love again after the death of her husband. When wealthy Englischer Kade Saunders rents her guest cottage for a month, Sadie's world is turned upside-down. Kade has a five-year-old autistic son who is unexpectedly left in his permanent care. As Sadie's feelings for the child grow, so do her feelings for Kade. But is this man suitable for anything more than friendship?